Метод аналізу показників ефективності автоматичної обробки двомірних інфрачервоних – зображень з використанням інтегральної фільтрації - Калашніков, О. С. (ХНУРЕ, 2021)
The reliability of the developed method should be considered as the probability of correct processing of results. It is formed as the inverse probability of the total probability of two wrong decisions. In order to increase the ability and effectiveness of point estimates of P1 and P2 first-line risks reflecting and the likelihood of these erroneous decisions, it is necessary to conduct multiple experiments to verify clearly defective samples and clearly defective ones.
Keywords: обробка зображень; використання інтегральної фільтрації